Analisis Respons Imun Ikan Koi (Cyprinus carpio Koi) yang Divaksin dengan Whole Protein Spora Myxobolus koi sebagai Kandidat Vaksin Myxobolusis [ Immune Response Analysis of Fish Koi (Cyprinus carpio Koi) Vaccinated Myxobolus Koi Spores Whole Protein as Vaccine Candidate Myxobolusis] - Gunanti Mahasri; Mohamad Yusuf; Mufasirin Mufasirin (Faculty of Fisheries and Marine Universitas Airlangga, 2015)
Abstract Myxobolus is one of parasites on koi fish that belongs to a class myxosporea that can infect and systemic and can cause harm to the fish farming. Vaccination is an attempt to cause-specific endurance through vaccination. Observations differential leukocytes and increased optical density values can be used to determine the effectiveness of the vaccine is given. This study aims to analyze the immune response koi fish vaccinated with Myxobolus koi spores whole protein for vaccine development myxobolusis in koi fish. The method used in this study is Completely Randomized Design with 4 treatments and 5 replications. The results showed that a change in the total number and types of leukocytes that can be used as indicators of the presence of certain infectious diseases that occure in fish. The highest value of lymphocytes in treatment B, monocytes highest in treatment D, neutrophils on treatment D, eosinophils on treatment A and basophils highest in treatment A. The observation of the highest optical density value in treatment B (fish vaccinated and infected 80 M. koi spores / tail) of 0.593 at day 30, while the lowest in treatment D (fish are not vaccinated but diinveksi 80 M. koi spores / tail) of 0,064 in 30 days